2002
DOI: 10.1152/ajpheart.00206.2001
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure and greater infarct expansion in middle-aged mice: a relevant model for postinfarction failure

Abstract: Young mice tolerate myocardial loss after coronary artery ligation (CAL) without congestive heart failure (CHF) signs or mortality. We predicted a CHF phenotype after CAL in aged mice. Left coronary artery ligation produced permanent myocardial infarcts (MI). Mortality was higher in male 14-mo-old C57BL/6N mice (Older mice) than in 2-mo-old mice (Young mice) (16 of 25 Older mice died vs. 0 of 10 Young mice, P < 0.02). After 8 wk, rales, weight loss, and lethargy preceded deaths. Captopril (50 mg x kg(-1) x day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 22 publications
4
59
1
Order By: Relevance
“…Ligation of the left anterior descending (LAD) coronary artery or one of its branches remains the most preferred and acceptable method of inducing regional injury and subsequent HF in rodents [10,85], as well as to gain further insight into pathophysiology of post-myocardial infarction (MI) cardiac remodeling [12,223]. The mechanisms responsible for cardiac remodeling are mostly related to changes in extracellular matrix of the remaining overloaded myocardium and neurohumoral activation [72,156,234].…”
Section: Myocardial Infarction-induced Hfmentioning
confidence: 99%
See 1 more Smart Citation
“…Ligation of the left anterior descending (LAD) coronary artery or one of its branches remains the most preferred and acceptable method of inducing regional injury and subsequent HF in rodents [10,85], as well as to gain further insight into pathophysiology of post-myocardial infarction (MI) cardiac remodeling [12,223]. The mechanisms responsible for cardiac remodeling are mostly related to changes in extracellular matrix of the remaining overloaded myocardium and neurohumoral activation [72,156,234].…”
Section: Myocardial Infarction-induced Hfmentioning
confidence: 99%
“…Generally, the infarct extension needs to affect at least 30% of the LV mass in order to present the typical characteristics of CHF and to induce considerable increases in the molecular markers of hypertrophy [10]. Age also exerts a noteworthy effect on the time course of CHF development, with young animals tolerating well LAD ligation without CHF signs, in spite of the larger infarct size [85]. Some recent studies showed that female mice undergo less extensive ventricular remodeling, suggesting the influence of sex hormones as a putative explanation for gender differences [315].…”
Section: Myocardial Infarction-induced Hfmentioning
confidence: 99%
“…The progressive structural changes and functional declines make the aging heart more susceptible to ischemia/reperfusion injury and contribute to increased cardiovascular mortality and morbidity in the elderly (Boengler et al 2009). Considerable evidence from animal studies and clinical observations indicates that aging hearts suffer from greater infarct expansion, more cell death, and poorer clinical outcome (White et al 1996;Gould et al 2002;Ananthakrishnan et al 2011). However, the mechanisms responsible for this age-related pathologic change remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] We have previously established in a model of mouse MI that, compared with young animals, aged mice demonstrate greater infarct expansion and less effective myocardial repair. 6 Defective scar formation arises from a decreased number of myofibroblasts and diminished collagen deposition in the infarct, which results in a structurally unstable scar formed by loose connective tissue. 7 Evidence indicates that multipotent cells can be generated in vitro from several adult organs including the heart.…”
mentioning
confidence: 99%
“…8 The ability of the progenitor cells to participate in scar formation, in particular insofar as maturation of fibroblasts into myofibroblasts, decreases with age. 6,7 We isolated cardiac resident MSCs from young and aged mice and compared their multipotentiality. MSCs derived from aged animals exhibited diminished expression of Nanog and increased adipocytic potential.…”
mentioning
confidence: 99%